A COMPARISON OF ALFRED NORTH WHITEHEAD'S AND CARL GUSTAV JUNG'S IDEA OF RELIGION: . - Chae Young, Kim (Journal of Dharma, 2002)
Whitehead and lung did not start their academic profession as a process philosopher or a depth psychologist. They did not study philosophy and psychology in the department of philosophy or psychology. Later, they created their own specific field in philosophy or psychology. They are not the philosopher or the psychologist who simply followed and maintained the basic system of philosophy or psychology.